2016
DOI: 10.1002/jrs.5056
|View full text |Cite
|
Sign up to set email alerts
|

Tracking photo‐degradation of triarylmethane dyes with surface‐enhanced Raman spectroscopy

Abstract: The triarylmethane dyes, basic fuchsine, methyl violet, and crystal violet, were some of the first synthetic colorants to be produced after the revolutionary invention of mauve in 1856. While their attractive pink‐to‐violet hues made them immediately interesting to the textile industry and the arts, they are prone to fade when exposed to light. This work aims to investigate basic fuchsine, methyl violet, and crystal violet and their degradation products through surface‐enhanced Raman spectroscopy (SERS), explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 28 publications
5
33
0
Order By: Relevance
“…Interestingly, the hydrogenated Ta 2 O 5 substrate exhibited a much better Raman enhancement ability than the Ta 2 O 5 NR substrates when detecting 10 −6 m MV, whereas its SERS behavior was regretfully much inferior to that of the 15%-Mo-Ta 2 O 5 substrate (Figure 3a). [39] As anticipated, when we gradually incorporated high-valence Mo 6+ into the Ta 2 O 5 NR substrate, its SERS performance obviously became superior to that of the pure Ta 2 O 5 NRs. The three main SERS peaks of MV on our 15%-Mo-Ta 2 O 5 substrates located at 1617 cm −1 (the totally symmetric 8a benzene mode), 1371 (phenyl-N stretching, asymmetric stretching of the central CCC bonds, bending of the ring CCC and CH bonds), and 1179 cm −1 (asymmetric 9a benzene mode, asymmetric stretching of the central CCC bonds).…”
Section: Raman Enhancement For the Ta 2 O 5 Samplesupporting
confidence: 52%
See 1 more Smart Citation
“…Interestingly, the hydrogenated Ta 2 O 5 substrate exhibited a much better Raman enhancement ability than the Ta 2 O 5 NR substrates when detecting 10 −6 m MV, whereas its SERS behavior was regretfully much inferior to that of the 15%-Mo-Ta 2 O 5 substrate (Figure 3a). [39] As anticipated, when we gradually incorporated high-valence Mo 6+ into the Ta 2 O 5 NR substrate, its SERS performance obviously became superior to that of the pure Ta 2 O 5 NRs. The three main SERS peaks of MV on our 15%-Mo-Ta 2 O 5 substrates located at 1617 cm −1 (the totally symmetric 8a benzene mode), 1371 (phenyl-N stretching, asymmetric stretching of the central CCC bonds, bending of the ring CCC and CH bonds), and 1179 cm −1 (asymmetric 9a benzene mode, asymmetric stretching of the central CCC bonds).…”
Section: Raman Enhancement For the Ta 2 O 5 Samplesupporting
confidence: 52%
“…ε 1 and ε 2 refer to the real and imaginary parts, respectively, of the substrates' dielectric constant and ε 0 is the real part of the dielectric constant of the surrounding medium. [39] Apparently, the SERS spectra of MV on our Ta 2 O 5 substrates were considerably dominated by the nontotally symmetric e vibrations, indicating a dominant CT or molecular resonances in this case. From Formula (2), there are three parts in the denominator jointly contributing to the SERS intensity.…”
Section: The Sers Enhancement Mechanism Of Ta 2 O 5 Substrates By Difmentioning
confidence: 71%
“…18,19 Furthermore, SERS has sensibly expanded the range of measurable materials due to efficient quenching of the molecular uorescence interferences of natural and articial dyes. 20 As a result, many authors have reported successful investigations of lakes and dyestuffs in archaeological textile bers 6,21 and paper and woodblock prints 22 and the identication of dye contents in pastel colors,…”
Section: -8mentioning
confidence: 99%
“…In this case, enhancement factors that are approximately the product of the enhancement factors of the non-resonant SERS substrate and the resonant Raman spectrum of the analyte were obtained. 22 Molecular resonance conditions could also be responsible for the appearance of the Raman bands of the red dye components in the SERS spectra of the historical and contemporary blue Caran D'Ache inks.…”
mentioning
confidence: 99%
“…Cesaratto, Lombardi, and Leona described tracking photo‐degradation of triarylmethane dyes with SERS. Their work aimed in particular to investigate basic fuchsine, methyl violet, and crystal violet and their degradation products through SERS, exploiting its high sensitivity and minimal sample requirement . Doherty et al studied Tyrian purple in archaeological textiles after DMF extraction and recrystallization for Raman identification of precursors and derivatives.…”
Section: Art and Archaeologymentioning
confidence: 99%